The Translation of Slang and Swear Words in Deadpool Movie: The Analysis of Equivalence in the Source and Target Language - Ajeng Mediastri Karinda (Passage, 2017)
This qualitative descriptive study aims to analyze the equivalence technique in English-Bahasa Indonesia translation of slang and swear words in Deadpool movie. The concept of formal and dynamic equivalences which is proposed by Nida (1964) is applied in this study as the theoretical framework. Slang and swear words were identified prior to equivalence analysis. For identification, this study applied two concepts: Yule’s (1996) word formation processes and Finegan’s (2004) lexical semantics. The study found 320 slang and swear words. Synonymy is the most frequent slang and swear words type which appears 145 times (45.31%). In terms of equivalence techniques, this study found that both formal and dynamic techniques are applied by the subtitler. However, dynamic technique is applied more frequently, 200 times (62.50%), than formal technique, 54 times (16.87%). Therefore, in this study, a synonymy-dynamic pattern is the most dominant. Furthermore, a high frequency of untranslated swear words, 66 times (20.62%) is another important phenomenon. Thus, the results indicate that even though the subtitle tends to convey the message of the source language by finding the most natural and the closest equivalences of the original slang and swear words, there is also an ethical or politeness consideration to omit a number of ‘rude’ and ‘abusive’ swear words in the target language. Keywords: slang and swear words types, subtitling, equivalence, formal and dynamic techniques